Rancang bangun Kontrol dan Monitoring pada Prototype Emergency Solar Runway Edge Light - Taryana; Van Bronson, Castro (Politeknik Penerbangan Makassar, 2021)
The need for remote control systems is increasing, making it easier for humans to be able to optimize performance on the job at any time. The purpose of this study is to design a light control system as in the case of the runway at one of Indonesia's airports that occurred short on both circuit. As a result, a number of airport flights were diverted to other airports, usually we use emergency lights. This research aims to control the prototype emergency solar runway edge light by using a long-distance radio frequency communication tool in two directions. Arduino Nano 328 microcontroller is used as a tool to process data from the system that serves to send commands to the client module and send current and voltage sensor data to the console module to be displayed in the monitoring system. The methodology used is the method of Literature, Observation and tool design, Programming language used is C. with this system makes it easier for more practical operation of lights